From Model‐based to Model and Simulation‐based Systems Architectures—Achieving Quality Engineering through Descriptive and Analytical Models. Issue 1 (11th April 2023) - Nowodzienski, Pierre; Navas, Juan
ABSTRACT: Systems architecture design is a key activity that affects the overall systems engineering cost. Hence it is fundamental to ensure that the system architecture reaches a proper quality. In this paper, we leverage model‐based systems engineering (MBSE) approaches and complement them with simulation techniques, as a promising way to improve the quality of the system architecture definition, and to come up with innovative solutions while securing the systems engineering process.